Behaviour of Groundwater Table with Rainfall in North-West Region of Bangladesh (Bangladesh Rice Journal, 2023)
Groundwater is the major source of water to meet up the vast domestic and agricultural demand in Bangladesh. Additionally, reduction in reliable surface water resources resulting the increased reliance on groundwater day by day. Therefore, monitoring the groundwater fluctuation over time is crucial to ensure the sustainable use of groundwater resources in future. The present study analyzed historical groundwater data to know the behaviour of groundwater at four locations of two districts Pabna and Rangpur in the North-Eastern part of the country. Historical groundwater level data and monthly rainfall data from 1989 to 2017 were collected from Bangladesh Water Development Board and Bangladesh Meteorological Department, respectively. The annual maximum groundwater table depth (MaxGWT) and minimum groundwater table depth (MinGWT) and its trend was analyzed, and positive and negative recharge years were identified from these values. We found the maximum declining rate at 6.6 cm annually and the maximum 205 cm total depletion in the study area. The number of years of negative recharge is more than that of positive recharge for 32 years. As a result, a declining trend in groundwater table was found at three locations of the study area. The maximum groundwater table remains below suction limit at Ishwardi, causes no shallow tubewell (STW) works during that period. A declining trend in annual rainfall is observed in Pabna district. A linear relationship between rainfall and recharge was found at two locations of the study area.Bangladesh Rice J. 25 (2) : 85-95, 2021